Reducing Dissemination of Viruses from Computer Touchscreens through Patient Hand Hygiene and an Automated Ultraviolet-C Touchscreen Disinfection Device. (4th October 2017) - Alhmidi, Heba; Cadnum, Jennifer; Piedrahita, Christina; John, Amrita; Donskey, Curtis
Abstract: Background: Computer touchscreens in patient waiting areas are a potential source for spread of viral and bacterial pathogens in healthcare facilities. Patient hand hygiene is recommended to prevent acquisition of pathogens on hands. Methods: We tested the efficacy of patient hand hygiene alone or in combination with a novel automated ultraviolet-C (UV-C) touchscreen disinfection device for reduction in dissemination of the nonpathogenic non-enveloped virus bacteriophage MS2 from contaminated touchscreens. Subjects randomized to control, alcohol hand sanitizer (10 or 30 second application), UV-C (30-second cycle), or alcohol hand sanitizer plus UV-C contacted 4 sites routinely used during operation of the touchscreen and then fingerpads were cultured. The log plaque-forming units (PFU) recovered were compared for each group. Patients were observed to determine the frequency of hand hygiene after use of a touchscreen in a waiting area. Results: As shown in the figure, the mean log10 PFU of bacteriophage MS2 recovered from fingerpads was significantly reduced by each of the interventions ( P < 0.001). However, only the combination of hand hygiene and UV-C was effective in completely preventing virus transfer. Of 20 patients observed in a waiting area, 0 (0%) used hand sanitizer that was available adjacent to the touchscreen. Conclusion: Our results suggest that use of alcohol hand sanitizer alone or in combination with an automated UV-C touchscreen disinfection device could reduce transmission of viruses from contaminated touchscreens. There is a need for education of patients on the importance of hand hygiene after contact with touchscreens. Disclosures: All authors: No reported disclosures.